Pengaruh Pijat Oksitosin Menggunakan Minyak Aromaterapi Lavender Terhadap Produksi ASI Ibu Nifas - Rika Ayunda Mega; Enny Yuliaswati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Mother's Milk (ASI) is nutrition for babies which is important especially in the first month of life, in Indonesia exclusive breastfeeding is as much as 66.1% where this figure is still below the expected target, one of which is not achieving exclusive breastfeeding is due to excessive breastfeeding not smooth in the early postpartum. One way to overcome the problem of breast milk production is to do an oxytocin massage using lavender aromatherapy oil. This study aims to determine the effect of oxytocin massage using lavender aromatherapy oil on the milk production of postpartum mothers. The type of research used is Quasi Experiment with Pre-Post Test With Nonequivalent Control Group. The sample technique used was purvosive sampling with a total sample of 31 respondents, divided into two groups, namely 15 intervention groups and 15 control groups. The research instrument uses an observation sheet. Data analysis used the Mann-Whitney test. Statistical test results using the Mann-Whitney Sig (2-tailed) = 0.006 <0.05 There is a significant difference in the average milk production between the treatment group and the control group. The conclusion is that there is an effect of oxytocin massage using lavender aromatherapy oil on the milk production of postpartum mothers.